Assistance of mulberry (Morus Alba, Sp.) cultivation in the Griya Caraka Resident - Fitri Dian Perwitasari; Arie Susetio Utami; Johan Johan; Aan Kunaedi; M. Nana Trisolvena (Universitas Muhammadiyah Magelang, 2022)
Mulberry is a traditional Indonesian medicine that is widely used due to the antioxidants found in mulberry leaves. Alkaloids, flavonoids, polyphenols, and terpenoids, which act as antioxidants, are found in mulberry leaves. This community service project aims to raise awareness about the health and economic benefits of mulberry. The method used is counseling and mentoring in January – June 2020. As a result of this program, a mulberry garden has been established in the Griya Caraka residential park, which has numerous advantages. Starting with the mulberry fruit, which can be eaten raw or cooked, and the mulberry leaf, which can be used to make mulberry leaf chips, mulberry leaf tea, and silkworm feed. Furthermore, the public can learn about the health benefits and nutritional value of mulberry plants, as well as process mulberry leaf chips under the Morrus Berry trademark